ECO-EDUTOURISM POTENTIAL FOR SUPPORTING FIELD RESEARCH CENTRE UGM IN KULONPROGO - Denni Susanto; Adi Nugroho; Wiyono Wiyono; Rochmad Hidayat (Gorontalo Journal of Forestry Research, 2021)
Edu-ecotourism is a combination between ecotourism with educational purpose. Nowadays edu-ecotourism is gaining popularity, even regencies across Indonesia labelled edu-ecotourism as their long term program. This research aimed to identify edu-ecotourism potential around Field Research Centre (FRC) in Kulonprogo. Research was done between April â€“ October 2020 taking place in area surrounding the Field Research Centre Sekolah Vokasi Universitas Gadjah Mada, Wates, Kulonprogo. Qualitative approach by using triangulation method was used during the research. Samples was taken by questioning 70 people around Field Research Centre UGM. Descriptive qualitative analysis was used to analyzing the result. Result showed that 32% citizen was not yet knowing about FRC. Meanwhile, 68% of them was already know about FRC. Some potential in the area that could be developed as edu-ecotourism such as: community forest ( as the result of national forest rehabilitation movement), cultural heritage (Tugu Pagoda and Bale Agoeng), education of red lemongrass cultivation, emping melinjo, and batik craft,Â  omah coklat makaryo, springs potential and better accessibility. Based on overall interview with the community, they also support the development of FRC as edu-ecotourism destination in Kulonprogo.